Data-driven modelling of mechanical properties - Chang, Eldridge Wen Wei (Nanyang Technological University, 2022)
Computational simulation of mechanical structures is an important tool for the design and optimization of structural components and the control of new processes. However, for simulations to be predictive, it is necessary to generate models that can accurately describe the mechanical properties of materials under different states of stress. These constitutive laws are often determined on an ad-hoc basis, by fitting the results of standard mechanical tests to phenomenological models.